Growth and yield patterns of black locust (Robinia pseudoacacia L.) sample trees affected by site conditions: case studies - Rédei, Károly; Szabó, Fruzsina; Honfy, Veronika; Ábri, Tamás (Acta Agraria Debreceniensis, 2023)
The trees removed from the long-term experiment plots are available for the measurements as lying trees. Through the determination of the volume in sections along the stem, the stem form, the stem volume and other factors can be specified. The comparison of the stems of individual trees of first and third yield classes of black locust (Robinia pseudoacacia L.) stands shows that site conditions have a main effect on the yield (mean tree volume). The difference can be as high as 53% at the age of 30 depending on the sites. To determine the growth patterns based on tree volume is rather a new approach in the light of the relevant literature. The obtained results also highlight the importance of choosing the appropriate tree species for a given site.